Virtual Working Environment: How to Manage and What is the Benefit & Challenges - Nurul Hazieatul Che Ri,; Ismail, Fadillah; Chan Shiau Wei, (Advances in Humanities and Contemporary Studies, 2021)
A virtual work environment or a virtual workplace is a workplace which exists digitally. It does not have a physical presence. It is created and maintained with the help of the internet. A virtual workforce can lower your costs and even increase productivity by keeping your overhead expenses low and allows companies to offer their employees more flexibility and give them more control over their daily schedule. On the flip side of the coin some studies shows that managers are ill-prepared to manage virtual workers and struggle with coordinating remote employees. Recognizing this fact, this article will present some suggestions and state the benefits and challenges that need to be faced in managing and implementing virtual environment in the workplace